The internet and Al Qaeda how bin Laden uses technology for his cause - Silm, Bouchaib (2016)
RECENTLY, Al Qaeda in Iraq, led by Abu Musab Al Zarqawi, released a 16-minute videotape and posted it on a Jihadist website. The video showcases the top ten operations carried out by Al Zarqawi’s group, the Base of Jihad in the Land of the Two Rivers (Iraq) and another group known as the Iraqi Islamic Army. The targets were the Americans and their soldiers and facilities in Iraq. The video pictures the destruction of cars, soldiers and building with Islamic songs (nashid) in the background, praising jihad and promising the Ummah of victory. A statement that accompanies the video says: “This videotape will be a storm for the Americans and will put the Americans in shame as it will show their soldiers injured, killed and their sophisticated weapons destroyed.”